The Effect Of Chemically Modified Lignin As A Filler In Ultraviolet Curable Resin System - Koay , Ee Ling (2011)

(untitled)
Alcell lignin was used as filler and reactive component in a ultraviolet (UV) curable system. In the preliminary study, different parameters have been used such as type of photoinitiator, percentage of photoinitiators and to determine suitable photoinitiator in the presence of lignin. The results showed gel content of the film of free radical photoinitiator has higher efficiency than cationic photoinitiator. Subsequently, the effect of lignin content in UV curable system was studied. The results indicated that the hardness of film increase as the lignin content was increased to the optimum point (10%), after which it decreased.